Eco Innovation Effort : A Review Of Dynamic Eco Innovation Practices And New Research Agenda Towards Sustainability Development - Abdul Rashid, Nurulizwa; Shamee, Samer Ali; Jabar, Juhaini (ISSR Journals, 2014)
-